Policy Analysis to Improve Teacher Professionalism in the Primary School Education System - Nur Afira; Putri Intan Berliana; Rizki Ananda; Syahril Siddik (Universitas Muhammadiyah Enrekang, 2023)
This study aims to analyze policies that can be used to improve teacher professionalism in the primary school education system. Teacher professionalism has a crucial role in creating an effective learning environment and has a positive influence on student development. However, challenges remain that hinder the improvement of teacher professionalism in many countries, including the need for improvements in education policy. This research uses a qualitative approach by collecting data through literature studies and relevant policy analysis. The results of the research that emerged in this study are the need for improved education and training for teachers, the construction of a comprehensive performance evaluation system, and better recognition and incentives for teachers who show commitment and excellence in their work. In addition, the importance of collaboration between government, schools, and communities in supporting teacher professional development is also highlighted.